Report on professional attachment with Wong Mun Piaw & Co. - Mao, Elizabeth Hwai May. (2008)
The purpose of this report is to review the professional attachment at Wong Mun Piaw & Co, an audit firm. This report gives an insight of the variable experience gained and the knowledge acquired during the 2 months of attachment.